2022
DOI: 10.3389/fnins.2022.893587
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensory Contributions of E-Cigarette Additives on Nicotine Use

Abstract: While rates of smoking combustible cigarettes in the United States have trended down in recent years, use of electronic cigarettes (e-cigarettes) has dramatically increased, especially among adolescents. The vast majority of e-cigarette users consume “flavored” products that contain a variety of chemosensory-rich additives, and recent literature suggests that these additives have led to the current “teen vaping epidemic.” This review, covering research from both human and rodent models, provides a comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 213 publications
0
3
0
Order By: Relevance
“…A key finding of our study is that e-cigarette users face the highest odds of developing sensory disorders compared to other groups. The review of Johnson et al 14 demonstrated that little is known about the sensory effects of e-cigarettes. However, as more nicotine is added to e-cigarette liquids, users increasingly perceive irritation and bitterness over time 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key finding of our study is that e-cigarette users face the highest odds of developing sensory disorders compared to other groups. The review of Johnson et al 14 demonstrated that little is known about the sensory effects of e-cigarettes. However, as more nicotine is added to e-cigarette liquids, users increasingly perceive irritation and bitterness over time 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The review of Johnson et al 14 demonstrated that little is known about the sensory effects of e-cigarettes. However, as more nicotine is added to e-cigarette liquids, users increasingly perceive irritation and bitterness over time 14 . This revelation heightens concerns about the potential health risks tied to e-cigarette use, especially given the growing trend of use among adolescents and young adults 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, supertasters are also less likely to smoke cigarettes (Keller et al, 2013). The smoking experience early in use is highly influenced by chemosensory stimuli (e.g., flavors, bitter tastes, unpleasant/pleasant odors) and it is suspected that supertasters are hypersensitive to the bitter components in both combustible and electronic cigarettes (Bartoshuk et al, 1994;Keller et al, 2013;Wickham, 2015;Risso et al, 2016;Mead et al, 2019;Wickham, 2020;Hayes and Baker, 2022;Johnson et al, 2022;Wickham et al, 2022).…”
Section: Research Questionmentioning
confidence: 99%